(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Menstruation is a physiological phenomenon for any female starts at the age of 11-15 years (menarche) and for most of the women end (menopause) by 45-50 years. The normal menstrual cycle relies on the action and interaction of hormones released from hypothalamic-pituitary-ovarian axes. With beginning of COVID-19 a lot of discussions on impact of this pandemic on women’s menstruation indicated that women may experience menstrual changes. Unfortunately it is currently unclear how many women have experienced menstrual cycle changes and is it exactly caused by this exposure? Still unknown. This study was done to confirm or exclude this observation A prospective cross-sectional study was conducted in Basrah Iraq from November 2020 to November 2021 . 150 Women who previously had normal cycle, experienced menstrual irregularity six months after infected with COVID 19 pandemic was encouraged to voluntarily participate by direct questionnaires and filled the predesigned questionnaire paper. The questionnaire consist of four domain : The first domain : consist of socio –demographic with mean age 30.8±9.1. The second domain : include the type of menstrual cycle patterns : risk of amenorrhea in this study is only 37.3% , menorrhagia is high 46% , dysmenorrhea 45.3% and 40.7% cycle length more than 35 days The third domain : estimated relation of state of vaccination with menstrual irregularity which reveal significant association between vaccination and dysmenorrhea with P-value 0.049 , the fourth domain: estimated relationship between ( menorrhagia and dysmenorrhea ) and patient’s health ,physical, psychological and social activities which showed menorrhagia(heavy cycle) and dysmenorrhea has a negative impact on women’s physical and psychological aspect with P-value 0.023 , 0.001 respectively. This study showed some sort of menstrual irregularity like increasing rate of dysmenorrhea ,heavy cycle and significant association of vaccination with dysmenorrhea but still not conclusive due to smaller sample size. So larger sample size more cohort studies is needed to confirm this association